Multi-threaded distributed system simulations using the transmission line element method. (October 2016) - Braun, R; Krus, P
By introducing physically motivated time delays, simulation models can be partitioned into decoupled independent sub-models. This enables parallel simulations on multi-core processors. An automatic algorithm is used for partitioning and running distributed system simulations. Methods for sorting and distributing components for good load balancing have been developed. Mathematical correctness during simulation is maintained by a busy-waiting thread synchronization algorithm. Independence between sub-models is achieved by using the transmission line element method. In contrast to the more commonly used centralized solvers, this method uses distributed solvers with physically motivated time delays, making simulations inherently parallel. Results show that simulation speed increases almost proportionally to the number of processor cores in the case of large models. However, overhead time costs mean that models need to be over a certain size to benefit from parallelization.